Nasiona szałwii hiszpańskiej (Salvia Hispanica L.) jako źródło składników wykazujących dobroczynny wpływ na ludzki organizm = Chia seeds (Salvia hispanica L.) as a source of ingredients with beneficial influence on human organism - Grzegorz Dąbrowski; Marta Skrajda (Kazimierz Wielki University, 2015)
Dąbrowski Grzegorz, Skrajda Marta. Nasiona szałwii hiszpańskiej (Salvia hispanica L.) jako źródło składników wykazujących dobroczynny wpływ na ludzki organizm = Chia seeds (Salvia hispanica L.) as a source of ingredients with beneficial influence on human organism. Journal of Education, Health and Sport. 2015;5(9):337-350. ISSN 2391-8306. DOI10.5281/zenodo.30929 http://dx.doi.org/10.5281/zenodo.30929 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A337-350 https://pbn.nauka.gov.pl/works/624246 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 12.09.2015.   NASIONA SZAŁWII HISZPAŃSKIEJ (SALVIA HISPANICA L.) JAKO ŹRÓDŁO SKŁADNIKÓW WYKAZUJĄCYCH DOBROCZYNNY WPŁYW NA LUDZKI ORGANIZM   Chia seeds (Salvia hispanica L.) as a source of ingredients with beneficial influence on human organism   Grzegorz Dąbrowski, Marta Skrajda   Katedra Przetwórstwa i Chemii Surowców Roślinnych Wydział Nauki o Żywności, Uniwersytet Warmińsko-Mazurski w Olsztynie   Uniwersytet Warmińsko-Mazurski w Olsztynie Katedra Przetwórstwa i Chemii Surowców Roślinnych Pl. Cieszyński 1, 10-726 Olsztyn e-mail: grzegorz.dabrowski@uwm.edu.pl   Abstrakt Nasiona szałwii hiszpańskiej były jednym z najważniejszych źródeł pożywienia cywilizacji środkowoamerykańskich z czasów przedkolumbijskich. Z żywieniowego punktu widzenia bardzo interesujący jest ich skład chemiczny. Zawierają one duże ilości polienowych kwasów tłuszczowych. Najbardziej wartościowy jest kwas α-linolenowy, który ma między innymi zdolność zapobiegania chorobie wieńcowej i cukrzycy. Obecność kwasów fenolowych, tokoferoli i flawonoidów pomaga zapewnić stabilność oksydacyjną tłuszczu z nasion szałwii. Zawierają one duże ilości frakcji błonnika pokarmowego. Zawartość nierozpuszczalnej frakcji błonnika jest od 4 do 5 razy wyższa niż frakcji nierozpuszczalnej. Stosunek ten jest korzystny i może odgrywać rolę przy obniżaniu poziomu cholesterolu we krwi. Frakcja białkowa nasion szałwii zawiera duże ilości aminokwasów egzogennych i może być źródłem bioaktywnych peptydów. Słowa kluczowe: Salvia hispanica L., polienowe kwasy tłuszczowe, włókno pokarmowe, przeciwutleniacze, białka.   Abstract Chia (Salvia hispanica L.) seeds were one of the most important sources of food for Central American civilizations in pre-Columbian times. The chemical composition of chia seeds is very interesting from nutritional point of view. It contains large amounts of polyunsaturated fatty acids. Most valuable is α-linoleic acid that can be helpful in between in coronary heart disease or diabetes prevention. The presence of phenolic acids, tocopherols and flavonoids helps to provide oxidative stability of oil from chia seeds. Chia seeds contain large amounts of dietary fiber. Content of insoluble fraction of dietary fiber is 4-5 times higher than soluble. It is good proportion and it can be helpful in lowering cholesterol content in blood. Protein fraction of chia contains high content of exogenous amino acids and can be potential source of bioactive peptides.   Key words: Salvia hispanica L., polyunsaturated fatty acids, dietary fiber, antioxidants, proteins.